A Novel Chloroplast Protein RNA Processing 8 Is Required for the Expression of Chloroplast Genes and Chloroplast Development in Arabidopsis thaliana - Kong, Mengmeng; Wu, Yaozong; Wang, Ziyuan; Qu, Wantong; Lan, Yixin; Chen, Xin; Liu, Yanyun; Shahnaz, Perveen; Yang, Zhongnan; Yu, Qingbo; Mi, Hualing (Frontiers in Plant Science, 2021)
Chloroplast development involves the coordinated expression of both plastids- and nuclear-encoded genes in higher plants. However, the underlying mechanism still remains largely unknown. In this study, we isolated and characterized an Arabidopsis mutant with an albino lethality phenotype named RNA processing 8 (rp8). Genetic complementation analysis demonstrated that the gene AT4G37920 (RP8) was responsible for the mutated phenotype. The RP8 gene was strongly expressed in photosynthetic tissues at both transcription and translation protein levels. The RP8 protein is localized in the chloroplast and associated with the thylakoid. Disruption of the RP8 gene led to a defect in the accumulation of the rpoA mature transcript, which reduced the level of the RpoA protein, and affected the transcription of PEP-dependent genes. The abundance of the chloroplast rRNA, including 23S, 16S, 4.5S, and 5S rRNA, were reduced in the rp8 mutant, respectively, and the amounts of chloroplast ribosome proteins, such as, PRPS1(uS1c), PRPS5(uS5c), PRPL2 (uL2c), and PRPL4 (uL4c), were substantially decreased in the rp8 mutant, which indicated that knockout of RP8 seriously affected chloroplast translational machinery. Accordingly, the accumulation of photosynthetic proteins was seriously reduced. Taken together, these results indicate that the RP8 protein plays an important regulatory role in the rpoA transcript processing, which is required for the expression of chloroplast genes and chloroplast development in Arabidopsis.